1981
DOI: 10.1111/j.1398-9995.1981.tb01841.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis in Danish General Practice

Abstract: The prevalence rate of allergic rhinitis and the consultation rate caused by this disease were studied in 131 general practices covering a population of 450,000 persons in Denmark. During a 1-year period starting June 1977 all consultations with or without symptoms were recorded. Allergic rhinitis was defined as paroxysmal sneezing and rhinorrhoea with or without conjunctivitis, and without signs of infection. Results are presented from three groups of practices classified by self-estimated completeness of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 2 publications
4
29
0
Order By: Relevance
“…These results coincide with those of other articles. It has been reported that in adolescents, the prevalence of PAR in males is slightly higher than that in females but that with age, the tendency reverses and there is no difference in prevalence of PAR between the sexes overall (14,15).…”
Section: Discussionmentioning
confidence: 96%
“…These results coincide with those of other articles. It has been reported that in adolescents, the prevalence of PAR in males is slightly higher than that in females but that with age, the tendency reverses and there is no difference in prevalence of PAR between the sexes overall (14,15).…”
Section: Discussionmentioning
confidence: 96%
“…First, we investigated patients who consulted their general practitioner because of chronic or recurrent nasal symptoms. Many of these patients did not have symptoms at the moment they consulted their general practitioner: a Danish study reported that only 20%-25% of allergic rhinitis patients had symptoms when they consulted their general practitioner (17). As eosinophilia is correlated with exposure to allergens, it has been recommended that asymptomatic patients are asked to return when they experience symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The children exposed to smoke had a significantly higher frequency of not just allergic reactions, but also non-specific reactions such as bronchitis and bronchial hyperreactivity [26]. In a Danish study [27], this value was 66%; exposure to tobacco smoke was established by measuring levels of cotinine (a nicotine metabolite) in the urine or serum [28].…”
Section: Discussionmentioning
confidence: 99%